2022
DOI: 10.1101/2022.02.20.481222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of caloric restriction on adipose tissue and metabolic health are sex- and age-dependent

Abstract: Caloric restriction (CR) is a nutritional intervention that reduces the risk of age-related diseases in numerous species, including humans. CR's metabolic effects, including decreased fat mass and improved insulin sensitivity, play an important role in its broader health benefits. However, the extent and basis of sex differences in CR's health benefits are unknown. We found that 30% CR in young (3-month-old) male mice decreased fat mass and improved glucose tolerance and insulin sensitivity, whereas these effe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 140 publications
(306 reference statements)
6
9
0
Order By: Relevance
“…Consistent with this, we find that CR suppresses energy expenditure more in young females than in young males, at least during the first week of CR ( Figure 3A–B ). In contrast, CR males and females have similar energy expenditure at week 3 of CR ( Figure 3A–B ), similar to our previous findings at week 4 of CR ( Suchacki et al, 2022 ). Consistent with this, BAT activity is similar between AL and CR mice after 6 weeks of CR ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with this, we find that CR suppresses energy expenditure more in young females than in young males, at least during the first week of CR ( Figure 3A–B ). In contrast, CR males and females have similar energy expenditure at week 3 of CR ( Figure 3A–B ), similar to our previous findings at week 4 of CR ( Suchacki et al, 2022 ). Consistent with this, BAT activity is similar between AL and CR mice after 6 weeks of CR ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 91%
“…Another advance over our previous calorimetry studies ( Suchacki et al, 2022 ) is that, by using the higher-sensitivity Promethion system, we were able to measure RER and thereby identify sex differences in lipid metabolism. We find that, compared to CR males, CR females have greater postprandial lipogenesis but lower FA oxidation and lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is not readily apparent why women in the IFT group experienced greater changes compared to those in the CERT group. Some previous studies in animal models have demonstrated sex-specific changes in response to calorie restriction [ 28 , 29 ], and it is possible that hormonal, divergent nutrient-sensing pathway activation in response to energy restriction and other mechanisms may be at play [ 30 ]. Nonetheless, in humans, research comparing CER and IF in females specifically have shown no differences in changes to TC or LDL-C (albeit utilizing endurance rather than resistance training) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the duration, magnitude, and pattern of food restriction, as well as macronutrient composition are known to impact the physiological responses to dietary manipulations 22,[37][38][39] . Moreover, whilst we focussed our study on the adult visual cortex, it remains unclear if the brain shows similar sex-specific energy-saving adaptations in other cortical areas, and how such adaptations change with age 6,40 .…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…These adaptations have been well documented for peripheral tissues and are sex-specific. For example, females, as compared to males, readily lose muscle and bone mass to reduce peripheral energy expenditure during food restriction, but lose less fat mass and overall bodyweight [1][2][3][4][5][6] . Moreover, females are more likely to suppress energy-costly, reproductive functions during food restriction than males, evidenced by substantive reductions in uterine and ovarian mass, as well as a cessation of reproductive function and behaviour [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%